Toripalimab plus chemotherapy vs. chemotherapy in patients with advanced non-small-cell lung cancer: A cost-effectiveness analysis - Huo, Gengwei; Liu, Wenjie; Kang, Shuo; Chen, Peng (Frontiers in Pharmacology, 2023)
Background: The potency and safety of toripalimab combination with chemotherapy (TC) as the first-line therapy for advanced NSCLC have been demonstrated in the CHOICE-01 study. Our research explored whether TC was cost-effective compared to chemotherapy alone from the Chinese payer perspective. Materials and Methods: Clinical parameters were obtained from a randomized, multicenter, registrational, placebo-controlled, double-blind, phase III trial. A Markov model with three mutually exclusive health statuses PFS, disease progression, and death) was used to predict the disease course. The main endpoints of the model included cost, QALYs, and incremental ICER. Univariate and probabilistic sensitivity analyses were performed to investigate the uncertainty. Subgroup analyses were performed to verify the cost-effectiveness of TC in patients with squamous and non-squamous cancer. Results: TC combination therapy yielded an incremental 0.54 QALYs with an incremental cost of 11,777, compared to chemotherapy, giving rise to ICERs of 21,811.76/QALY. Probabilistic sensitivity analysis revealed that TC was not favorable at 1 time GDP per capita. With a prespecified WTP of three times the GDP per capita, combined treatment had a 100% probability of being cost-effective and had substantial cost-effectiveness in advanced NSCLC. Probabilistic sensitivity analyses showed that TC was more likely to be accepted with a WTP threshold higher than 22,195 in NSCLC. Univariate sensitivity analysis showed that the utility of PFS state, crossover proportions of the chemotherapy arm, cost per cycle of pemetrexed treatment, and discount rate were the dominant influencing factors. Subgroup analyses found that in patients with squamous NSCLC, the ICER was 14,966.09/QALY. In the nonsquamous NSCLC, ICER raised to 23,836.27/QALY. ICERs were sensitive to the variance of the PFS state utility. TC was more likely to be accepted when WTP increases exceeded 14,908 in the squamous NSCLC subgroup and 23,409 in the non-squamous NSCLC subgroup. Conclusion: From the perspective of the Chinese healthcare system, TC may be cost-effective in individuals with previously untreated advanced NSCLC at the prespecified WTP threshold compared to chemotherapy, and more significant in individuals with squamous NSCLC, which will provide evidence for clinicians to make the best decisions in general clinical practice.